A comparative evaluation of a new fully automated assay for von Willebrand factor collagen binding activity to an established method. Issue 1 (22nd November 2017) - Stufano, F.; Baronciani, L.; Mane‐Padros, D.; Cozzi, G.; Faraudo, S.; Peyvandi, F.
Abstract : Introduction: Laboratory diagnosis of von Willebrand disease (VWD) is made by the measurement of von Willebrand factor (VWF) protein level and its activities. Current VWF activity tests include ristocetin cofactor and collagen binding (VWF:CB) assays. Aim: We have undertaken an evaluation of a new fully automated VWF:CB assay relative to an established enzyme‐linked immunosorbent assay (ELISA) method. Methods: The two analytical systems operate with different detection principles: a chemiluminescent method performed on ACL AcuStar Analyzer (the former) and a colorimetric ELISA by Asserachrom Stago (the latter) (type III collagen from human placenta). The HemosIL AcuStar VWF:CB assay is a chemiluminescent 2‐step immunoassay that uses magnetic particles coated with a type III collagen triple‐helical peptide. VWF:CB levels were determined in 50 healthy subjects and 100 VWD patients (22 type 1, 73 type 2 and 5 type 3). Results: Eleven VWD samples reported VWF:CB values below the lower detection limit of one or both methods. The new method showed a good correlation with the ELISA method ( r > .9, mean bias 3.85 IU/dL) in both healthy and VWD samples. One of 150 samples gave inconsistent results using the two assays, leading to an uncertain diagnosis of VWD type 1 (ELISA method) or type 2 MCB (fully automated method). Conclusion: The new assay is rapid and simple to use, with its ready‐to‐use reagent cartridges. This VWF:CB assay, in addition to the measurement of VWF:Ag and VWF:RCo made on the same platform, gives additional information for the diagnosis of VWD in both nonspecialized and reference laboratories.